Digital Marketing Assistance as a Business Development Effort in the Home Industry in Kalidawir Tanggulangin Sidoarjo Village - Rohtih, Wiwin Ainis; Rahman, Uskar; Rochma, Nur (Amalee: Indonesian Journal of Community Research and Engagement, 2024)
Digital marketing assistance is one of the strategic efforts of business actors to expand market reach and develop their product businesses. This service aims to provide digital marketing assistance to develop businesses in the home industry of Kalidawir Village, Tanggulangin, Sidoarjo. This service method uses Participatory Action Research (PAR). The PAR method has work steps that provide an active role for all parties in designing, implementing, and evaluating changes to the business they are engaged in. This assistance was carried out in Kalidawir Village, Tanggulangin District, Sidoarjo Regency. The results of this assistance service obtained knowledge and skills for home industry actors that are in line with the current digital era. The assisted subjects also shared the results and lessons learned with the surrounding community, such as PKK mothers and Asman toga administrators. This sharing can ultimately result in an exchange of knowledge and inspiration between business actors in the village so that Kalidawir Village can become one of the important economic centers in Tanggulangin District.